A comparative study of adoption of dairy farm technologies between non-members and members of dairy co-operative villages - KUNZRU, O N; TRIPATHI, HEMA (The Indian Journal of Animal Sciences, 2013)
The study was carried out in 12 villages of Bareilly district in Uttar Pradesh. Personal interview schedule was administered on randomly selectcd dairy owning 96 rural women from dairy co-operative system (MC) and96 rural women from non-member villages (NMC). Data were collected on 10 independent variables and adoption behaviour in relation to 5 dairy farm technologies, viz. adoption of AI in cattle and buffaloes, vaccination of ammals against contagious diseases, cultivation of green fodder, feeding green fodder and feeding concentrates to dairy animals. In both the MC and NMC systems, all the respondentsowning land were cultivating green fodder. All other technologies were to have been found adopted at higher levels in MC systems than in NMC system. The overall extent of adoption in both the systems was at medium level. About 23% of respondents of MC system fell in high level of overall adoption against about 5% of respondents in NMC system. Further, mean scores of adoption with regard to all the 5 technologies werefound higher in MC system. Correlation analysis revealed positive and highly significant relationship (p